2010
DOI: 10.1007/s11947-009-0299-3
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Microextraction (SPME) Techniques for Quality Characterization of Food Products: A Review

Abstract: Solid-phase microextraction (SPME) is a relatively new sampling technique wherein sample extraction and pre-concentration could be achieved in a single step. The handling of an SPME device is simple, and the analysis of volatiles could be easy. However, the process becomes complex while analyzing sample matrices of heterogeneous nature. The complexity also increases depending upon the nature of compounds to be extracted. Careful selection and optimization of extraction parameters like fiber coating selection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(101 citation statements)
references
References 123 publications
2
97
0
2
Order By: Relevance
“…Advances in sample preparation aim to minimize laboratory solvent use and hazardous waste production, save employee labor and time, and reduce the cost per sample, while improving the efficiency of the analyte isolation. This includes the development and application of molecularly imprinted polymers in food sample analysis [3], the use of monoliths in sample preparation and analysis of milk [4], the development of porous monolith microextraction techniques for determination of veterinary residues in food matrices by [5], the use of the so-called QuEChERS (quick, easy, cheap, effective, rugged, and safe) methodology for determining pesticide residues in food matrices [6], the application of immunoaffinity column clean-up techniques in food analysis [7], the development of solid-phase microextraction (SPME) techniques for quality characterization of food products [8], the application of ultrasound-assisted extraction to the determination of contaminants in food and soil samples [9], and the use of liquid phase microextraction in food analysis [10]. Besides, some papers have focused on the description of sample preparation strategies used for the analysis of aflatoxins in food and feed [11], antibacterial residues in foodstuffs [12], or the determination of pesticides in foods [13].…”
Section: Food Analysis: Current State Of the Art Methodologies And mentioning
confidence: 99%
“…Advances in sample preparation aim to minimize laboratory solvent use and hazardous waste production, save employee labor and time, and reduce the cost per sample, while improving the efficiency of the analyte isolation. This includes the development and application of molecularly imprinted polymers in food sample analysis [3], the use of monoliths in sample preparation and analysis of milk [4], the development of porous monolith microextraction techniques for determination of veterinary residues in food matrices by [5], the use of the so-called QuEChERS (quick, easy, cheap, effective, rugged, and safe) methodology for determining pesticide residues in food matrices [6], the application of immunoaffinity column clean-up techniques in food analysis [7], the development of solid-phase microextraction (SPME) techniques for quality characterization of food products [8], the application of ultrasound-assisted extraction to the determination of contaminants in food and soil samples [9], and the use of liquid phase microextraction in food analysis [10]. Besides, some papers have focused on the description of sample preparation strategies used for the analysis of aflatoxins in food and feed [11], antibacterial residues in foodstuffs [12], or the determination of pesticides in foods [13].…”
Section: Food Analysis: Current State Of the Art Methodologies And mentioning
confidence: 99%
“…The analysis also showed that the wort fermentation changes the color profile, depending on whether the yeast is microencapsulated or free. To verify changes in headspace flavors, the GC/MS-SPME was used (Balasubramanian and Panigrahi 2010). This technique allowed a rapid characterization and identification of VOCs in the headspace, indicating possible marker molecules.…”
Section: Color Profilementioning
confidence: 99%
“…An important step for determination of an analyte in real samples is sample preparation that affect the selectivity and sensitivity of the analysis method. Nowadays, due to several advantages such as reducing matrix effects and interfering species, and preconcentration of the analyte, microextraction methods are widely used as sample preparation method for real samples such as biological and Pharmaceutical, water and wastewater, industrial and food samples [14][15][16][17]. Dispersive solid phase microexrtraction is a new, rapid and practical method for extraction of various analytes using a dispersing solid sorbent to separate then from the sample solution [18,19].…”
Section: Introductionmentioning
confidence: 99%